STRATEGI PENGEMBANGAN USAHATANI KAKAO DI DESA TAKATUNGA 1 KECAMATAN GOLEWA SELATAN KABUPATEN NGADA: Strategy For Developing Cocoa Farming Business In Takatunga 1 Village, South Golewa Sub-District, Ngada Regency - Victoria Ayu Puspita; Maria Natalia Bupu; Victoria Coo Lea (Jurnal AGRIBIS, 2026)
Cocoa farming is one of the main sources of livelihood for the people of Takatunga 1 Village, South Golewa District, Ngada Regency. However, its development still faces several challenges such as limited capital, pest and disease attacks, and price fluctuations that affect farmers' income. This study aims to identify the internal and external factors that influence cocoa farming and to formulate strategies for its development in Takatunga 1 Village, South Golewa District, Ngada Regency. The research method uses a descriptive approach with SWOT analysis through the formation of IFAS, EFAS, IE matrices, and SWOT matrix analysis. The results of the study indicate that internal factors include strengths such as good quality cocoa beans, sufficient land area, and farmers' experience in cocoa cultivation, while the main weaknesses are pest and disease attacks, limited capital, and low knowledge of cultivation technology. External factors consists of opportunities in the form of high market demand and government support, while threats come from cocoa price fluctuations and market competition. The IE matrix analysis places the position of the cocoa farming business in Takatunga 1 Village in quadrant II (grow and build), so the appropriate SO strategy is an intensive strategy through market penetration and product development. Thus, the development of cocoa farming can be directed towards improving product quality, expanding market access through cooperation with cooperatives or buyers from other regions, and increasing farmer capacity through counseling and training.